Analysis of Secondary Leukemia and Myelodysplastic Syndrome After Chemotherapy for Solid Organ Tumors Using the Food and Drug Administration Adverse Event Reporting System (FAERS) - Takehiro Kawashiri; Daisuke Kobayashi; Mayako Uchida; Shiori Hiromoto; Masashi Inoue; Hajime Ikeda; Mizuki Inoue; Takao Shimazoe (Frontiers Media S.A., 2021)
Purpose: As the prognosis of cancer patients deteriorates, secondary carcinogenesis after chemotherapy, especially secondary hematological malignancies, becomes a serious problem. However, information on the frequency and time of onset of secondary hematological malignancies and the risk of hematological malignancy with different drugs is scarce. This study aimed to evaluate the incidence of leukemia and myelodysplastic syndrome in patients with solid tumors, including breast, colon, gastric, pancreatic, small cell lung, non-small cell lung, esophageal, ovarian, cervical, and endometrial cancers. Methods: Using the United States Food and Drug Administration Adverse Event Reporting System, we analyzed the reporting rates, reporting odds ratios, and the reporting onset times of secondary leukemia and myelodysplastic syndrome for each drug used. Results: The leukemia reporting rates were higher in breast, small cell lung, ovarian, and endometrial cancers than in other cancers, and the myelodysplastic syndrome reporting rates were higher in ovarian and endometrial cancers than in other cancers. For each cancer type, the reporting odds ratios of cytocidal anticancer agents, such as taxanes, anthracyclines, alkylating agents, platinum, and topoisomerase inhibitors, were higher than those of other drugs. Alternatively, the reporting odds ratios of molecular targeted drugs and immune checkpoint inhibitors were not higher than those of other drugs. Approximately half of the cases of leukemia and myelodysplastic syndrome were reported within 1 to 4 years after chemotherapy. Conclusions: Our study clarified the risks of leukemia and myelodysplastic syndrome for several anticancer drugs in patients with solid tumors. Our data may aid in the assessment of the risks of secondary leukemia and myelodysplastic syndrome when medical oncologists, clinical pharmacists, and patients select chemotherapy regimens.